Physiological and angiographic outcomes of PCI in calcified lesions after rotational atherectomy or intravascular lithotripsy. (14th October 2021) - Gallinoro, E; Monizzi, G; Candreva, A; Sonck, J; Mileva, N; Mastrangelo, A; Andreini, D; Bartorelli, A L; Galli, S; Nagumo, S; Munhoz, D; Barbato, E; et al.
Abstract: Background: Percutaneous coronary interventions (PCI) in calcified coronary artery lesions is associated with impaired stent expansion, higher rate of periprocedural complications and cardiac mortality. Lesion preparation using dedicated calcium modifying techniques such as RA or IVL has been advocated. Studies comparing these technologies are lacking. Objectives: To compare the in-stent pressure gradient, evaluated by virtual fractional flow-reserve, in calcific lesions treated using either rotational atherectomy (RA) or intravascular lithotripsy (IVL). Methods: Patients undergoing either RA- or IVL-assisted PCI from two European centers were included. Propensity score matching (1:2) was performed to control for potential bias. Primary outcome was post- PCI in-stent pressure gradient calculated by virtual fractional flow reserve (vFFRgrad, calculated as the difference between the vFFR at the proximal minus distal edge of the stent). Secondary outcomes included the proportion of patients with complete functional revascularization defined as of distal vFFR post PCI (vFFRpost) ≥0.90. Results: From a cohort of 210 patients, 105 matched patients (70 RA and 35 IVL) were included. Pre-PCI vFFR did not differ between groups (0, 65±0, 13 RA and 0, 67±0, 11 IVL). After PCI, in-stent pressure gradient was significantly lower in the IVL group (0.032±0.026 vs 0.043±0.026 in the RA group, p=0.024). The proportion of vessels with functional complete revascularization was similar between the two groups (32.9% vs. 37.1% in the RA and IVL group, respectively; p=0.669) Conclusions: Calcific lesions preparation with IVL is effective and resulted in improved in-stent pressure gradient compared to RA. Approximately one third of the patients undergoing PCI for a severely calcified lesion achieved functional revascularization with no difference between rotational RA and IVL. FUNDunding Acknowledgement: Type of funding sources: None.